FAMILY OESTRIDAE - Wolff, Marta; Grisales, Diana (Zootaxa, 2016)
The Oestridae of Colombia are poorly known. There are reports only for the genera Cuterebra, Dermatobia and Metacuterebra and three species, one species per genera.